Rickettsia parkeri rickettsiosis in different ecoological regions of Argentina and its association with Amblyomma tigrinum as a potential vector - Romer, Yamila (2014)
Rickettsia parkeri, a newly recognized tick-borne pathogen of humans in the Americas, is a confirmed cause of spotted fever group rickettsiosis in Argentina. Until recently, almost all cases of R. parkeri rickettsiosis in Argentina have originated from the Paraná River Delta, where entomological surveys have identified populations of R. parkeri-infected Amblyomma triste ticks. In this report, we describe confirmed cases of R. parkeri rickettsiosis from Córdoba and La Rioja provinces, which are located several hundred kilometers inland, and in a more arid ecological region, where A. triste ticks do not occur. Additionally, we identified questing A. tigrinum ticks naturally infected with R. parkeri in Córdoba province. These data provide evidence that another human-biting tick species serves as a potential vector of R. parkeri in Argentina and possibly, other countries of South America.